Analysis of Serum proteom before and after Intravenous Injection of wild ginseng herbal acupuncture - Tae-Sik Kang; Ki-Rok Kwon; Sun-Gu Lee (Korean Pharmacopuncture Institute, 2004)
Objectives : To observe changes in the serum proteins before and after intravenous injection of wild ginseng herbal acupuncture. Methods : Blood was collected before and after the administration of wild ginseng herbal acupuncture and only the serum was centrifuged. Then differences in the spots on the scanned image after running 2-Dimensional electrophoresis were located and conducted mass analysis and protein identification. Results : Following results were obtained from the comparative analysis of serum proteins before and after the administration of wild ginseng herbal acupuncture. 1. 28 spots were identified before and after the administration. 2. In confirming manifestation degree, spots with more than two-times increase were 204, 803, 1505, 2205, 3105, 7104, 9001 spots, with more than one-time increase were 1101, 1302, 2013, 3009, 3010, 4002, 4009, 6706, 7103, 8006, 8101, and spots with decrease were 205, 801, 3205, 5202, 6105. 3. After conducting protein identification, proteins 205, 804, 1302, 4009, 6105, 6106 are unidentified yet, and 1101 is unnamed protein. Protein 204 is identified as complement receptor CR2-C3d, 801 as YAP1 protein, 803 as antitrypsin polymer, 1505 as PRO0684, 2013 and 3010 as proapolipoprotein, 2205 as USP48, 2403 as vitamin D binding protein, 3009 as complement component 4A preprotein, 3105 as immunoglobulin lambda chain, 3205 as transthyretin, 4002 as Ras-related protein Ral-A, 4204 as beta actin, 5202 and 7104 as apolipoprotein L1, 6704 as alpha 2 macroglobulin precursor, 7103 as complement component 3 precursor, 8006 as testis-specific protein Y, 8101 as transferrin, 9001 as (Alpha-Oxy, Beta-(C112g)deoxy) T-State Human Hemoglobin, and 9003 as human hemoglobin. 4. Immune protein CR2-C3d, which acts against microbes and pathogenic organisms, and Antitrypsin(803), which is secreted with inflammatory response in the lungs, were increased by more than 200% after the administration of herbal acupuncture. 5. Immunoglobulin lambda chain(3105), Alpha-Oxy, Beta-(C112g)deoxy T-State Human Hemoglobin(9001), and human hemoglobin(9003) were increased by more than two-times after the administration of herbal acupuncture. 6. Proapolipoprotein(2013, 3010) and apolipoprotein(7104), key components of the HDL-cholesterol which plays an important role in preventing arteriosclerosis, were increased after the administration of herbal acupuncture. 7. Vitamin D binding protein(DBP, 2403), protecting the lung at the time of inflammatory response, was increased after the administration of herbal acupuncture. 8. Transthyretin(TTR, 3205), which is the main protein causing familial amyloid polyneuropathy(FAP), was decreased after the administration of herbal acupuncture. 9. Ras-related protein Ral-A(4002) that controls phospholipid metabolism, cytoskeletal formation, and membrane traffic, was increased after the administration of herbal acupuncture. 10. Testis-specific protein Y(8006), which takes part in determination of the gender, was increased by more than two-times after the administration of herbal acupuncture. 11. Transferrin(8101), T-State Human Hemoblobin(9001), and Human Hemoblobin(9003) which balances the iron level in the body, were increased after the administration of herbal acupuncture. Conclusion : Above results support the notion that intravenous injection of cultivated wild ginseng herbal acupuncture induce changes in serum proteins and this research can be a pioneer work in finding biomarkers.